Retail Employees’ Image on Shopping Destination: It’s Impact on Their Behavioural Intention - dwi suhartanto; Iwan Mulyawan; Eddy Syah Yahya; Gundur Leo (International Journal of Supply Chain Management, 2018)
The current development in retail industry shows that there is an intense competition between shopping destinations. In this competitive environment, an imperative strategy to endure and succeed is by developing a unique and favourable destination image. This study examines retail employee image on shopping destination model and its impact on their behaviour intention. This study uses 333 samples of retail employees collected from Bandung, Indonesia. The results verify the cognitive and affective component of image are critical drivers of shopping destination overall image. However, this study suggests that the overall image is not the determinant of behaviour intention. The cognitive image is the only important factor in determining retail employee behaviour intention. Further, this study shows that the differences between staff and manager on the destination image model are insignificant. The implication for retail business managers as part of the supply chain system in retail industry is discussed.